The Effect of Work-Life Balance on Employee Performance with the Role of Organizational Commitment as an Intervening Variable - Purba, Desvi Mahdia; Sanusi, Fauji; Kambara , Roni (Advances In Social Humanities Research, 2025)
The vaping product retail industry has shown significant growth in recent years. However, amidst increasing market demand, employee performance at PT. Sentra Jaya Sejahtera has experienced quite significant fluctuations. This condition indicates the need for an appropriate strategy to improve employee performance by identifying the factors that influence it. This study aims to analyze the effect of work-life balance on employee performance with the role of organizational commitment as an intervening variable. This study uses a quantitative approach with a population consisting of all employees of PT. Sentra Jaya Sejahtera. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.0 software. The results of the study indicate that: 1) Work-life balance has a positive and significant effect on employee performance, 2) Work-life balance has a positive effect on organizational commitment, 3) Organizational commitment has a positive and significant effect on employee performance, 4) Organizational commitment mediates the effect of work-life balance on employee performance.